Homology-based identification and structural analysis of Pangasius hypophthalmus Annexins and Serine proteases to search molecules for wound healing applications - Avila Rodríguez, Maria Isabela (2024)
Chronic wounds and burns are a worldwide healthcare problem that erodes patients’ well-being and healthcare systems. This silent and costly epidemic requires new, cost-efficient solutions to improve patients’ physical and economic welfare. Eschar-degrading vegetal and bacterial proteases have been utilized as a solution. However, these proteins are evolutionarily far from those present in human wound healing. Serine protease (SP) and annexin (ANX) proteins interact within the skin healing process. A homology-based identification pipeline can help in discovering selective human SP and ANX analogs in the epithelial tissue of the fast-healing species, Pangasius hypophthalmus. In the present work, we found 14 candidates for RT-PCR in P. hypophthalmus using homology inference. The genetically detected candidates were then structurally and sequentially analyzed to understand their possible relation to SPs and ANXs involved in human wound healing. A total of six TBLASTN/BLASTX candidates (four SPs and two ANXs) were detected in P. hypophthalmus skin. Structural analysis revealed that all SP candidates resembled human KLK4, KLK5, KLK6, and KLK8, whereas all ANX only resembled human ANXA4. Structure and sequence analysis revealed high conservation of ANX Ca2+ binding sites (GDXD) and SP catalytic triad (HDS) motifs. In addition, structural analysis revealed that SP substrate selectivity position 186 was the main difference between human KLK5 and P. hypophthalmus SPs. These findings may allow the proposal and testing of more selective formulations, broadening treatments beyond debridement.